Staged versus One-Time Complete Revascularization with Percutaneous Coronary Intervention in STEMI Patients with Multivessel Disease: A Systematic Review and Meta-Analysis. - Zhenwei Li; Yijiang Zhou; Qingqing Xu; Xiaomin Chen (PLoS ONE)
Introduction In patients with acute ST-elevation myocardial infarction (STEMI), the preferred intervention is percutaneous coronary intervention (PCI).Whether staged PCI (S-PCI) or one-time complete PCI (MV-PCI) is more beneficial and safer in terms of treating the non-culprit vessel during the primary PCI procedure is unclear. We performed a meta-analysis of all randomized and non-randomized controlled trials comparing S-PCI with MV-PCI in patients with acute STEMI and MVD. Methods Studies of STEMI with multivessel disease receiving primary PCI were searched in PUBMED, EMBASE and The Cochrane Register of Controlled Trials from January 2004 to December 2014. The primary end points were long-term rates of major adverse cardiovascular events and their components-mortality, reinfarction, and target-vessel revascularization. Data were combined using a fixed-effects model. Results Of 507 citations, 10 studies (4 randomized, 6 nonrandomized; 820 patients, 562 staged PCI and 347 one-time, complete multi-vessel PCI) were included. S-PCI compared to MV-PCI significantly reduced mortality both long-term (OR 0.44, 95% CI 0.29-0.66, P<0.0001, I2 = 0%) and short-term (OR 0.23, 95% CI 0.1-0.51, P = 0.0003, I2 = 0%). There was a trend toward reduced risk of MACE with s-PCI compared with MV-PCI (OR 0.83, 0.62-1.12, P = 0.22, I2 = 0%). No difference between S-PCI and MV-PCI was observed in reinfarction (OR 0.97, 0.61-1.55, P = 0.91, I2 = 0%), or target vessel revascularization (OR1.17, 95% CI 0.81-1.69, P = 0.40, I2 = 8%). Conclusions The staged strategy for non-culprit lesions improved short- and long-term survival and should remain the standard approach to primary PCI in patients with STEMI; one-time complete multivessel PCI may be associated with greater mortality risk. However, additional large, randomized trials are required to confirm the optimal timing of a staged procedure on the non-culprit vessel in STEMI.